Efficient tandem organic light-emitting device based on photovoltaic-type connector with positive cycle - Liu, Huihui (2013)
We designed a tandem organic light-emitting device based on an organic photovoltaic-type charge generation connector (CGC) of fullerene carbon 60/copper(II) phthalocyanine. The CGC can absorb a portion of photons radiated from emission zone and form excitons which disassociated into free charges at PN junction interface without energy barrier, leading to low driving voltage and better charge balance. The efficiency increases remarkably with increasing current density, even beyond two folds compared with single unit device under higher current density, meaning slower roll-off. The whole process is a positive cycle, and actually enhances the utilization of internal radiation and the overall performance of tandem device.